2021
DOI: 10.3390/ijms22169056
|View full text |Cite
|
Sign up to set email alerts
|

Diatoms and Plants Acyl-CoA:lysophosphatidylcholine Acyltransferases (LPCATs) Exhibit Diverse Substrate Specificity and Biochemical Properties

Abstract: The search of the Phaeodactylum tricornutum genome database revealed the existence of six genes potentially encoding lysophospholipid acyltransferases. One of these genes, Phatr3_J20460, after introduction to yeast ale1 mutant disrupted in the LPCAT gene, produced a very active acyl-CoA:lysophosphatidylcholine (LPCAT) enzyme. Using in vitro assays applying different radioactive and non-radioactive substrates and microsomal fractions from such yeast, we have characterized the biochemical properties and substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…8 ), probably providing PC for PDAT (utilizing PC as the acyl donor for TAG synthesis) to support the increase of TAG. It has been demonstrated that LPCAT utilizes the cytosolic acyl-CoA pool and lysophospholipids to regenerate PC and PE [ 60 ]. When the HL stress was removed, while many polar lipid synthetic genes did not or slightly recovered, several ones recovered considerably, including MDG (Phatr3_J54168), and PGPS (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…8 ), probably providing PC for PDAT (utilizing PC as the acyl donor for TAG synthesis) to support the increase of TAG. It has been demonstrated that LPCAT utilizes the cytosolic acyl-CoA pool and lysophospholipids to regenerate PC and PE [ 60 ]. When the HL stress was removed, while many polar lipid synthetic genes did not or slightly recovered, several ones recovered considerably, including MDG (Phatr3_J54168), and PGPS (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…tricorunutum culturing temperature, which is 19 o C [ 8 , 41 ]. Nevertheless, this enzyme also maintained a quite high activity at 20 o C reaching 79% of maximum activity at 30 o C. The disparity between the native temperature environment of an enzyme and its biochemical properties is a common characteristic among acyltransferases [ 33 , 42 , 43 ]. We cannot exclude, that observed discrepancies result from membrane composition differences between native membrane of diatom and yeast, in which their activity was tested.…”
Section: Discussionmentioning
confidence: 99%
“…The lysophosphatidylcholine acyltransferases (LPCATs) family contains four members, namely LPCAT1-4 [ 9 ]. LPCATs are crucial in lipid metabolism since they allow for the production of novel phospholipid molecules in a way that is separate from de novo synthesis [ 10 ].…”
Section: Discussionmentioning
confidence: 99%